THE IMPACT OF INTERNATIONAL INVESTMENT AGREEMENTS (IIAS) ON MANAGEMENT OF STATE PUBLIC SERVICES AND CONCESSIONS IN THAILAND - Tanchinwuttanakul, Kamol (Academic Journal Phranakhon Rajabhat University, 2021)
This research “The Impact of International Investment Agreements (IIAs) on Management of State Public Services and Concessions in Thailand” is based on hypotheses that International Investment Agreements (IIAs) supposes the Impact to Internal legal system as public law in Thailand according to state public services and concessions especially under principle of administrative contract (le contrat administrative). The legal research method is studying the model of the Legal Positivism school which emphasize method of deduction in legal documents, textbooks, provisions of international investment law, models of IIAs and arbitral awards including comparison with IIAs of the other important countries for understanding in contexts as substantive clauses of IIAs which refer to National Treatment, Most Favored Nation (MFN), Fair and Equitable Treatment (FET), Umbrella Clause, Expropriation and Settlement of Disputes. The researcher found that the Impact of International Investment Agreements (IIAs) on Management of State Public Services and Concessions in Thailand is fact. In summary, the substantive clauses in IIAs reduces the sovereignty of Thailand to manage state public services and concessions and for legal interpretation in principle of public law and administrative law should be consistent with substantive clauses in IIAs and foreign investors under scope of IIAs will choose the settlement dispute by international arbitral tribunal under IIAs and not consider about Thai courts. The recommendations from this research is Thailand should study deeply in substantive clauses of IIAs before negotiation. The application of principles of public and administrative law to the establishment of public services and concessions should consider about IIAs and should have an understanding in process of International Arbitral tribunal also.